Pengaruh Self Control, Change Readiness dan Sistem Informasi terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening pada Kantor Badan Perencanaan Pembangunan Daerah Kota Padang Panjang - Risse Putri Afrieni; Yamasitha Yamasitha (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This study aims to determine the effect of Self Control, Change Readiness and Information Systems on Employee Performance with Job Satisfaction as an Intervening Variable at the Padang Panjang City Regional Development Planning Agency Office, under the guidance of Mr. Yamasitha, SE.MM and Ibuk Chintya Ones Charli, SE.MM. This study is a quantitative study. The method of data collection through questionnaires, with a sample of 33 respondents at the Padang Panjang City Regional Development Planning Agency Office. The analysis methods used are path analysis, partial least squares (PLS) analysis, outer model, inner model and hypothesis testing. Data processing in this study used the SmartPLS 4.0 software program. The results of the study can be concluded that Self Control has a positive and significant effect on Job Satisfaction, Change Readiness has a positive and insignificant effect on Job Satisfaction, Information Systems have a positive and insignificant effect on Job Satisfaction, Self Control has a positive and significant effect on Employee Performance, Change Readiness has a positive and insignificant effect on Employee Performance, Information Systems have a positive and insignificant effect on Employee Performance, Job Satisfaction has a positive and significant effect on Employee Performance, Self Control has a positive and significant effect on Employee Performance through Job Satisfaction as an Intervening Variable, Change Readiness has a positive and insignificant effect on Employee Performance through Job Satisfaction as an Intervening Variable, Information Systems have a positive and insignificant effect on Employee Performance through Job Satisfaction as an Intervening Variable at the Padang Panjang City Regional Development Planning Agency Office.